Induced Emission on Transitions from Vibrational Excited Levels of the KrF Molecule - Sofia Yampolskaya; Arcady Yastremskii; Yuri Panchenko; Alexey Puchikin; Sergey Bobrovnikov (Photonics)
The paper considers the possibility of extending the spectral region of the wavelength tuning of a discharge KrF amplifier due to induced transitions from the vibrational excited states of the electronic level B. The model of the KrF amplifier on a He/Kr/F2 mixture is presented, in which the behavior of the vibrational level populations is consistent with the excitation conditions of the active medium. The simulation results show that the shift in the operating wavelength to the short-wavelength region is possible in excitation modes, when the birth rate of excimer molecules is greater than the rate of their relaxation from upper to lower vibrational levels. The theoretical dependences of gain on the wavelength for different pressures were obtained. They confirm the possibility of tuning the KrF amplifier wavelength in the range of up to 10 nm while maintaining a gain of at least 0.5 of its maximum value.